Experiences of LGBTQ+ graduate students in research-focused doctoral programs: a scoping review - Baldwin-SoRelle, Carrie; McDonald, David A. (Frontiers in Education, 2024)
BACKGROUND: Students of sexual and gender minority (SGM) identities have long been underserved in higher education, and the limited research thus far has focused on undergraduates. There is a large gap in understanding the outcomes and experiences of LGBTQ+ graduate students, particularly in STEM.OBJECTIVE: We undertook the first scoping review to examine the available literature on LGBTQ+ student experiences in research-focused doctoral programs. A scoping review methodology was utilized to compile a broad set of publications for a narrative review of emergent themes. METHODS: A comprehensive search of 5 bibliographic databases yielded 1,971 unique studies, which were screened by two independent reviewers for data on LGBTQ+ doctoral students in non-clinical fields. Eighty-two publications were included in the analysis, over half of which were published in the past 5 years. RESULTS: Thirteen themes emerged from analyzing the included publications. LGBTQ+ identities can continue evolving during graduate school, and some students incorporated SGM identities in their research ("mesearch"). Though students expected academia to be welcoming, many encountered repeated anti-LGBTQ+ bias that impacted their perceived safety for coming out. Nearly half of the studies mentioned intersectionality with other marginalized identities, including race/ethnicity, religion, disability, and others. CONCLUSIONS: Based on the information presented, we outline recommendations for practitioners to improve doctoral education, such as preparing teaching assistants to manage discriminatory classroom conduct.